8-Oxo-7,8-dihydro-2′-deoxyguanosine values measured in brain DNA of rats upon investigating cortexin protective action - D. S. Esipov; O. V. Esipova; T. V. Zinevich; T. A. Gorbacheva; T. S. Nevredimova; A. L. Krushinsky; V. S. Kuzenkov; V. P. Reutov (Тонкие химические технологии, 2012)
The protective effect of cortexin was investigated with the use of acoustic stress hemorrhagic stroke model. A significant decrease of 8-oxo-2'-deoxyguanosine to 2'-deoxyguanosine ratio in the DNA molecule was shown using brain slices of cortexin treated Krushinsky-Molodkina rats.